2008
DOI: 10.1103/physrevb.78.094518
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties ofSmFeAsO1xFxas a probe of the interplay between electrons and phonons

Abstract: A comparative study of thermal properties of SmFeAsO, SmFeAs(O 0.93 F 0.07 ) and SmFeAs(O 0.85 F 0.15 ) samples is presented. Specific heat and thermal conductivity show clear evidences of the spin density wave (SDW) ordering below T SDW~1 35 K in undoped SmFeAsO. At low level of F-doping, SmFeAs(O 0.93 F 0.07 ), SDW ordering is suppressed and superconducting features are not yet optimally developed in both specific heat and thermal conductivity. At optimal level of F-doping SmFeAs(O 0.85 F 0.15 ) anomalies re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
43
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 45 publications
15
43
1
Order By: Relevance
“…C el and C ph are expressed as C el = γT and C ph = βT 3 at the low temperatures, where γ and β are electronic and phonon specific heat coefficients, respectively. As for the value of β, it is useful to refer to the result (β ∼ 0.36 mJ/mol K 4 ) of SmFeAs(O 1−x F x ) with the same structure [14,15]. We estimate the C mg of Sm 3+ f -moment for x = 0.075 by (C p − βT 3 )/T and calculate the corresponding entropy.…”
Section: B Resistivity and Seebeck Coefficientmentioning
confidence: 99%
“…C el and C ph are expressed as C el = γT and C ph = βT 3 at the low temperatures, where γ and β are electronic and phonon specific heat coefficients, respectively. As for the value of β, it is useful to refer to the result (β ∼ 0.36 mJ/mol K 4 ) of SmFeAs(O 1−x F x ) with the same structure [14,15]. We estimate the C mg of Sm 3+ f -moment for x = 0.075 by (C p − βT 3 )/T and calculate the corresponding entropy.…”
Section: B Resistivity and Seebeck Coefficientmentioning
confidence: 99%
“…Similar situation is found for SmFeAs(O 0.93 F 0.07 ). 28 Smaller j values in PrO 0.3 F 0.7 BiS 2 may represent the crystallographic disorder. An enhancement of j value above the superconducting temperature 5 K is due to the gap opening at the Fermi surface, followed by carrier condensation and consequent suppression of electron-phonon scattering.…”
Section: Introductionmentioning
confidence: 99%
“…͑1͒. 7,18 Thus, this approximation is TЈ dTЈ between 17 and 160 K can be fitted well ͑solid lines in Fig. 3 and its inset͒.…”
mentioning
confidence: 99%
“…17 A reliable estimation of the phonon background, therefore, appears to be the key for the analysis of specific-heat data. Tropeano et al 18 and Baker et al, 7 fortunately, have demonstrated that such a non-Debye trend may be caused by a large Einstein contribution and a rather low Debye temperature T D . The normal-state specific heat, C p,n , was therefore proposed as,…”
mentioning
confidence: 99%